(3Hjf GdfXQjI h GdJWHjb (B( (3VQjHI GdONd h VQjHI GdeHjYGJ aj GdGQOf (B)s - (3eMeO(B, (3GHh fUGQs; (3eMahX GdeTGYdI(B, (3aQGS YWG Gddg GdTghGfs ((3YeGf(B:s (3eWGHY GdOSJhQ GdJLGQjI(B,s, 2005)
(3GdJYQja HGdVQjHI h NUGFUgG , eONd dbGfhf VQjHI GdONd aj GdGQOf , eUGOQ GdONd GdNGVYI ddVQjHI h GdeYaGI efgG, fabGJ GdYed GdebHhdI h ZjQ GdebHhdI VQjHjG , GdGMcGe GdYGeI ,GdfhGMj GdGLQGFjI dbGfhf VQjHI GdONd , VQjHI GdONd Ydi GdQhGJH h GdGLhQ , eONd dGLQGAGJ GdJbOjQ Ydi eNJda Gdecdajf (B-(3Gdecdahf GdPjf dG jeSchf MSGHGJ CUhdjI (B- (3, bWGY TQcGJ GdGTNGU , bWGY GdTQcGJ GdJLGQjI h GdUfGYjI , bWGY TQcGJ GdebGhdGJ , bWGY GdUQGaI h GdhSGWI , bWGY TQcGJ GdJCejf , GdbWGY GdeUQaj h GdeGdj h GdTQcGJ GdJj JbHd GdhOGFY , GdeYGdLI GdeMGSHjI h GdbGfhfjI dVQjHI GdeHjYGJ (B.s
(3eQGLY U(B.509s
Keywords: (3GdVQGFHs; (3GdeMGSHI GdVQjHjI(B- (3GdCQOfs; (3VQjHI GdONd(B- (3GdCQOfs; (3eMGSHIs